Dynamic Modelling of the Relation between Bidding Strategy and Construction Project Performance. (2017) - Wibowo, Mochamad Agung; Astana, I. Nyoman Yudha; Rusdi, H.A.
Abstract: Strategy is required in order to win the competition. Bidding strategy in construction is defined as a management skill of using all available resources, both physical and financial, to offer a comprehensive and competitive bidding, with an aim to win the competition, and provide maximum project performance. There are many factors that influence construction bidding strategy, and many indicators of project performance have to be considered. Therefore, the relation between bidding strategy and project performance is very complex. Contractors have to consider this very carefully, and they have to evaluate their bidding strategies to ensure that the company goals have been achieved. Dynamic system is a method for develop a management simulation using computer, and helps the study of dynamic complexity; understand the source of policy resistance and helps the design of more effective policies. Furthermore, dynamic system is explained as a tool simulation system that is able to solve the problem of system complexity and also can present behaviour of real world. The study aims to develop a dynamic model and the simulation of bidding strategy and project performance. Case study was carried out in the major contractor in Denpasar, and the analysis used is System Dynamics. The model demonstrated that bidding strategy had a direct impact to project performance. The model simulation found that the enhancement of bidding strategy by 13.67% improved the project performance significantly, by 10.55%, from bid price.